2009
DOI: 10.1002/arch.20290
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal and nutritional regulation of insect fat body development and function

Abstract: The insect fat body is an organ analogue to vertebrate adipose tissue and liver and functions as a major organ for nutrient storage and energy metabolism. Similar to other larval organs, fat body undergoes a developmental ''remodeling'' process during the period of insect metamorphosis, with the massive destruction of obsolete larval tissues by programmed cell death and the simultaneous growth and differentiation of adult tissues from small clusters of progenitor cells. Genetic ablation of Drosophila fat body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
0
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 129 publications
(95 citation statements)
references
References 50 publications
2
87
0
6
Order By: Relevance
“…Bioenergetic studies clearly indicated UCP function in mitochondria isolated from both G. cocquereliana leg muscle and fat body tissue, the latter being an insect analogue tissue to vertebrate adipose tissue and liver functioning as a major organ for nutrient storage and energy metabolism (Liu et al 2009). The activity of the G. cocquereliana uncoupling protein (GcUCP) is stimulated by free fatty acids and inhibited by purine nucleotides (GTP).…”
Section: Discussionmentioning
confidence: 99%
“…Bioenergetic studies clearly indicated UCP function in mitochondria isolated from both G. cocquereliana leg muscle and fat body tissue, the latter being an insect analogue tissue to vertebrate adipose tissue and liver functioning as a major organ for nutrient storage and energy metabolism (Liu et al 2009). The activity of the G. cocquereliana uncoupling protein (GcUCP) is stimulated by free fatty acids and inhibited by purine nucleotides (GTP).…”
Section: Discussionmentioning
confidence: 99%
“…27,28,[34][35][36]60 Moreover, the 20E-induced autophagy and endocytosis crosstalk with each other and share some regulatory components, including PIK3C3/ VPS34. 61 The fat body functions as a major organ for nutrient storage and energy metabolism in insects; 22,32,33 therefore, the function of autophagy in exploiting remaining nutrients should be particularly important in this insect adipose tissue.…”
Section: E Upregulatesmentioning
confidence: 99%
“…It is considered to be the central organ that integrates and coordinates different hormonal and nutritional signals for regulating insect development and metamorphosis. 20,32,33 In the fat body of two lepidopteran species and Drosophila, 20E-induced developmental autophagy progressively occurs during the larvalprepupal transition, 21,27,28,[34][35][36][37] and in the Drosophila fat body, EcR is required for 20E to induce autophagy. 21 We have previously determined that in the Bombyx fat body, 20E upregulates apoptosis genes to induce some apoptotic events.…”
mentioning
confidence: 99%
“…1E). During the larval-pupal metamorphosis of Drosophila, the fat body undergoes a remodeling process but remains in the posterior part of the pupa (Nelliot et al, 2006;Liu et al, 2009). The posterior portion of the JH-deficient pupae often appeared to be empty, suggesting that JH has an important role in the control of fat body development during the larval-pupal transition.…”
Section: Research Articlementioning
confidence: 99%